A decisão do pedido incontroverso: aspectos gerais, natureza do provimento e repercussão recursal - Ataide, Ádia Kristianne Ataete Vilar (2011)
The reality of a slow and inefficient justice clashes with the social desire for a timely and effective adjudication. In confronting this challenge, are part of the reforms with the purpose accelerator, including the Law 10.444/2002 who inserted the paragraph 6 of Article 273 of the CPC. Starting from the premise that the process assumes deducted claim by one party and resisted by the other, with no resistance, seems unnecessary to delay the outcome of the process. If the absence of resistance has to put all the demand in court, has become the Trial of Early Total Lide, is part of it, Trial of Accelerated Partial Deal. There is no reason for the decisions are treated differently. So set the uncontroversial part through recognition of the request, confession, defense or sufficiency of evidence of a combined request or part of a single request, the judge makes his decision by deep cognition of matter. For the purposes of the institute, drawing its purpose, mister overcoming the principle of unity of the sentence, noting that other principles also occupy important role in the legal system, such as speed, access to justice and effectiveness. The relaxation of the principle of uniqueness of the sentence, does not represent a complete break with the procedural formalities, but the realization that it can achieve legal certainty, legal defense and contradictory, with other more effective mechanisms to put it right. This is the new vision of the process, not an end in itself, overcome obstacles and fulfill the ideal of justice effectively and quickly